2015
DOI: 10.1080/09639284.2015.1051561
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Intentions of Accounting Students in China to Pursue Certified Public Accountant Designation

Abstract: Based on the theory of planned behavior [Ajzen, I. (1991). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50(2), 179-211], we examine the factors influencing the decisions of accounting students in China concerning the certified public accountant (CPA) designation. Surveying 288 college accounting students, we find that genuine interest, perceived professional independence in the workplace and perceived difficulties in maintaining the certification all affect students' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 45 publications
3
55
5
4
Order By: Relevance
“…As Allen (2004) points out, the number of years required for qualifying and entering the accounting profession influence students' decision to pursue accounting. Wen et al (2015) also find perceived difficulties in maintaining professional accounting certification to be a key predictor of Chinese college accounting students' intention to pursue the Chinese Certified Public Accounting qualification.…”
Section: Career Choice Of Tertiary Students In Ghanamentioning
confidence: 87%
“…As Allen (2004) points out, the number of years required for qualifying and entering the accounting profession influence students' decision to pursue accounting. Wen et al (2015) also find perceived difficulties in maintaining professional accounting certification to be a key predictor of Chinese college accounting students' intention to pursue the Chinese Certified Public Accounting qualification.…”
Section: Career Choice Of Tertiary Students In Ghanamentioning
confidence: 87%
“…Another study by Wen, Hao and Bu also confirm that the combination of internal and external factors influences the accounting students in China to pursue a career as a Certified Public Accountant (CPA) [7]. The study reports that perceived independence and difficulties, as well as genuine interest and better market opportunities, affect students intending to pursue CPA.…”
Section: Introductionmentioning
confidence: 86%
“…Bogdan et al (2016) found out that there is a significant correlation between the scale of professional judgment in accounting and the opinion of students regarding the fact that high quality professional judgment is reflected in the preparation of relevant financial information. Wen et al (2015) examined "the factors influencing the decisions of accounting students in China concerning the certified public accountant (CPA) designation" (Wen et al 2015). Authors made the conclusion (Wen et al (2015)), that "students need to realize that accountants are more than number crunchers.…”
Section: Methodsmentioning
confidence: 99%
“…Wen et al (2015) examined "the factors influencing the decisions of accounting students in China concerning the certified public accountant (CPA) designation" (Wen et al 2015). Authors made the conclusion (Wen et al (2015)), that "students need to realize that accountants are more than number crunchers. Today's CPAs are engaged in many managerial functions besides bookkeeping: they are actively involved in business development, estate planning, management consulting, retirement and college planning, and investment counseling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation